2021
DOI: 10.1038/s41598-021-85851-w
|View full text |Cite
|
Sign up to set email alerts
|

Specific modulation of corticomuscular coherence during submaximal voluntary isometric, shortening and lengthening contractions

Abstract: During voluntary contractions, corticomuscular coherence (CMC) is thought to reflect a mutual interaction between cortical and muscle oscillatory activities, respectively measured by electroencephalography (EEG) and electromyography (EMG). However, it remains unclear whether CMC modulation would depend on the contribution of neural mechanisms acting at the spinal level. To this purpose, modulations of CMC were compared during submaximal isometric, shortening and lengthening contractions of the soleus (SOL) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…However, more recent studies conducted on isokinetic (Liu et al, 2019) or cyclical (Yoshida et al, 2017) contractions have shown that the CMC magnitude is not constant over the time-period corresponding to movement, and a recent study performed on healthy subjects engaged in a squat-like task revealed that the level of CMC was different according to either the concentric, eccentric or isometric movement phases (Kenville et al, 2020). Similarly, a recent study from our group (Glories et al, 2021) showed that CMC decreased in lengthening compared to isometric contractions. Taken together, these results raise an important methodological concern regarding CMC evaluation-namely the need for a novel dynamic analysis framework to account for the time-varying changes in CMC during the time course of movement execution -and hence the need to refine and enhance our understanding of its involvement in the functional coupling between brain and muscles.…”
Section: Introductionmentioning
confidence: 86%
“…However, more recent studies conducted on isokinetic (Liu et al, 2019) or cyclical (Yoshida et al, 2017) contractions have shown that the CMC magnitude is not constant over the time-period corresponding to movement, and a recent study performed on healthy subjects engaged in a squat-like task revealed that the level of CMC was different according to either the concentric, eccentric or isometric movement phases (Kenville et al, 2020). Similarly, a recent study from our group (Glories et al, 2021) showed that CMC decreased in lengthening compared to isometric contractions. Taken together, these results raise an important methodological concern regarding CMC evaluation-namely the need for a novel dynamic analysis framework to account for the time-varying changes in CMC during the time course of movement execution -and hence the need to refine and enhance our understanding of its involvement in the functional coupling between brain and muscles.…”
Section: Introductionmentioning
confidence: 86%
“…Cortico-muscular coupling (CMC) is a powerful analysis tool to investigate functional connectivity between the cerebral cortex and muscles across the body. CMC is known to take place with the Tibialis Anterior (TA) and Soleus (SO) muscles at beta (15–25 Hz) frequencies during isometric contraction and gamma (40–80 Hz) frequencies during isotonic contraction ( 13 , 14 ). In addition, several studies reported beta frequency coupling with the medial Gastrocnemius (MG) and TA muscles during cyclic ankle movements ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Electromyographic continuous data were band-stop filtered at 49–51 Hz ( Krauth et al, 2019 ) to remove power line noise. As was done in Fauvet et al (2019 , 2021) , Glories et al (2021) , and Delcamp et al (2022) , the EMG signal was then 3-100 Hz band-pass filtered to keep the denoised part of the EMG signal energy that is necessary for reliable quantification of intermuscular coherence in the frequency band of interest in the present study. All the filters were fourth-order, zero-lag Butterworth types.…”
Section: Methodsmentioning
confidence: 99%